Removal of basic nitrogen compounds from fuel oil with [C4mim]Br/ZnCl2 ionic liquid. (3rd July 2017) - Li, W. S.; Liu, J.
ABSTRACT: Metal-based ionic liquid [C4 mim]Br/ZnCl2 was synthesized, and its structure was characterized using FTIR spectroscopy and a mass spectrometer. The denitrogenation performance of the ionic liquid was investigated using coker diesel oil as feedstock. Experiment results showed that [C4 mim]Br/ZnCl2 presented a good denitrogenation performance, obtaining about 94.95% basic N-removal efficiency under the condition with a temperature of 50°C, 1:1 (w/w) IL:oil, extraction time of 30 min. In addition, the basic N-removal efficiency can still reach above 50% at 1:7 IL/oil (w/w) during four recycles of the ionic liquid.